Prevalence, risk factors and primary prevention of osteoarthritis in Asia: A scoping review - Sakinah, Harith; Nurulhuda, Mat Hassan; Nur Aimi Asyrani, Zamri (2019)
Introduction: Osteoarthritis (OA) is estimated to be the eleventh leading cause of disability worldwide. In Asian countries, OA is much less well-known than in the caucasian population and strongly associated with aging. Therefore, this article focuses comprehensively on the prevalence, risk factors and primary prevention for OA identified in Asian countries. Methods: This scoping review used the methodological framework by Arksey and O'Malley (2005). Pertaining to this topic, a comprehensive search on academic journals published from 2008 to 2018 (English) was conducted. Results: A total of 30 studies were selected in this review from 221,510 studies screened from electronic databases. The overall prevalence of OA is in a range of 20.5% to 68.0%. Most of the Asian populations reported to have knee OA in a range of 13.1% to 71.1% in various Asian countries. Risk factors that have been associated with OA are advanced age, being the female and obesity. Osteoporosis, higher body mass density, low level of education, family history of OA, smoking and environmental factors appeared as significant risk factors for OA. A strategic method of primary prevention for OA through lifestyle modification is reducing obesity and treating concomitant cardiovascular disease. Conclusion: Determining OA prevalence and risk factors will provide important information for planning future cost-effective preventive strategies.